Development of an Industry-Oriented Project-Based Learning Model in Culinary Arts Vocational Education: An ADDIE-Based Curriculum Innovation Framework - Tri Murhanjati Sholihah; prihastuti prihastuti; minta harsana; Ngabdul Munif; Rizki Hidayati; Yuni Triastuti Yuni Triastuti (Journal of Research in Social Science and Humanities, 2026)
The rapid transformation of the culinary industry has created new demands for vocational higher education institutions to produce graduates equipped with industry-relevant competencies. Despite continuous curriculum reforms, a significant gap remains between graduate competencies and industrial expectations, particularly in Culinary Arts vocational programs. This study aimed to develop and evaluate an industry-oriented Project-Based Learning (PjBL) model integrated into an Outcome-Based Education (OBE) curriculum framework using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The research adopted a Research and Development (RD) approach involving culinary industry representatives, lecturers, and students from the Applied Bachelor Program in Culinary Arts at Universitas Negeri Yogyakarta. Data were collected through questionnaires, interviews, observations, document analysis, and learning outcome assessments. Descriptive statistical analysis and paired sample t-tests were employed to examine the effectiveness of the developed learning model. Findings revealed that food safety standards, kitchen management, communication skills, and entrepreneurial competencies were the most highly prioritized competencies by industry stakeholders. Project-Based Learning emerged as the most preferred instructional strategy, supported by industry internships, collaborative assessments, and competency certification schemes. The implementation of the developed model significantly improved students’ competencies, with average learning achievement increasing from 67.53 in the pre-test to 82.67 in the post-test. The study concludes that integrating Project-Based Learning with industrial collaboration provides an effective mechanism for reducing the competency gap between vocational education and labor market demands. The proposed model offers a practical framework for vocational institutions seeking to enhance graduate employability and strengthen industry-academia partnerships.